Preliminary Evaluation of Rapid Visual Identification of Burkholderia pseudomallei Using a Newly Developed Lateral Flow Strip-Based Recombinase Polymerase Amplification (LF-RPA) System - Li, Jin; Zhong, Qiu; Shang, Mei-Yun; Li, Min; Jiang, Yuan-Su; Zou, Jia-Jun; Ma, Shan-Shan; Huang, Qing; Lu, Wei-Ping (Frontiers in Cellular and Infection Microbiology, 2022)
Burkholderia pseudomallei is an important infectious disease pathogen that can cause melioidosis. Melioidosis is mainly prevalent in Thailand, northern Australia and southern China and has become a global public health problem. Early identification of B. pseudomallei is of great significance for the diagnosis and prognosis of melioidosis. In this study, a simple and visual device combined with lateral flow strip-based recombinase polymerase amplification (LF-RPA) was developed, and the utility of the LF-RPA assay for identifying B. pseudomallei was evaluated. In order to screen out the optimal primer probe, a total of 16 pairs of specific primers targeting the orf2 gene of B. pseudomallei type III secretion system (T3SS) cluster genes were designed for screening, and F1/R3 was selected as an optimal set of primers for the identification of B. pseudomallei, and parameters for LF-RPA were optimized. The LF-RPA can be amplified at 30-45°C and complete the entire reaction in 5-30 min. This reaction does not cross-amplify the DNA of other non-B. pseudomallei species. The limit of detection (LOD) of this assay for B. pseudomallei genomic DNA was as low as 30 femtograms (fg), which was comparable to the results of real-time PCR. Moreover, 21 clinical B. pseudomallei isolates identified by 16S rRNA gene sequencing were retrospectively confirmed by the newly developed LF-RPA system. Our results showed that the newly developed LF-RPA system has a simple and short time of operation and has good application prospect in the identification of B. pseudomallei.